The challenges faced by Malaysian small medium entrepreneurs (SMEs) in export initiatives / Melissa Wee … [et al.] - Wee, Melissa; Mohd Zaki, Khaulah; Sadik, Mohd Zaki; Marmaya, Najihah Hanisah; Abdul Razak, Noraznira (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
The increasing number of SMEs in Malaysia indicate that there is a large potential for export opportunities. Realizing the 37% contribution to GDP by SMEs, it is essential to understand the challenges and hurdles faced by these entities when exporting products to other countries. The significance of this, study is that, it looks into the three main challenges faced by Malaysian SMEs, which are distribution access, human capital and market attractiveness as the exogenous variables of this study. A total of 70 questionnaires responded to by SME owners and managers, were utilised for this study and a two-stage analysis of PLS-SEM consisting of measurement and structural analysis were applied to this study. Results shown that only human capital is found to be a challenge for SMEs in Malaysia in matters pertaining to export.